1998
DOI: 10.1590/s0103-06631998000400008
|View full text |Cite
|
Sign up to set email alerts
|

The use of epinephrine-containing anesthetic solutions in cardiac patients: a survey

Abstract: A questionnaire survey of 150 last term dental students from four dental schools was performed to delineate their current opinion with regard to the use of epinephrine-containing anesthetic solutions for dental procedures in cardiac patients. The students provided their opinion as "contraindicated" or "not contraindicated" regarding the use of these solutions in eight cardiac patients with either stable or unstable heart diseases including ischemic heart disease, arrhythmia, hypertension, and heart failure. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…There are few studies on knowledge and attitudes of dentists towards other cardiac-related issues, such as managing antithrombotic medications, 24 , 25 , 30 resuscitation skills, 31 , 32 , 33 the use of AED, 33 , 34 and cardiac side effects of local dental anaesthesia. 35 , 36 Most dentists are more aware of older anticoagulant and antiplatelet medications than they are of novel anticoagulants. In general, dentists overestimate bleeding risks, which makes them overly cautious and steers them towards consulting a physician before performing invasive dental procedures on patients using anticoagulation treatment; thromboembolic events are their major concern.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on knowledge and attitudes of dentists towards other cardiac-related issues, such as managing antithrombotic medications, 24 , 25 , 30 resuscitation skills, 31 , 32 , 33 the use of AED, 33 , 34 and cardiac side effects of local dental anaesthesia. 35 , 36 Most dentists are more aware of older anticoagulant and antiplatelet medications than they are of novel anticoagulants. In general, dentists overestimate bleeding risks, which makes them overly cautious and steers them towards consulting a physician before performing invasive dental procedures on patients using anticoagulation treatment; thromboembolic events are their major concern.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of L100 or L80 with a large volume might lead to adverse effects in patients with cardiac diseases. Gerlach et al [ 21 ] suggested that epinephrine-containing anesthetics should be used under consideration of the cardiac condition of each patient; thus, minimum dosage of epinephrine is indicated in patients with significant cardiac diseases.…”
Section: Discussionmentioning
confidence: 99%